High-field MRI of hemorrhagic cortical infarction. - Hecht-Leavitt, C; Gomori, J M; Grossman, R I; Goldberg, H I; Hackney, D B; Zimmerman, R A; Bilaniuk, L T (American Journal of Neuroradiology, 1986)
High-field MRI is capable of differentiating acute, subacute, and chronic hemorrhagic cortical infarctions. In eight of nine patients, hemorrhage occurred in a vascular watershed zone. Acute hemorrhagic cortical infarction produces mild cortical low intensity on T2-weighted images outlined by subcortical edema (high intensity) and isointensity with normal cortex on T1-weighted images. Subacute hemorrhagic cortical infarction shows cortical high intensity first on T1-weighted images and later on T2-weighted images; it is also associated with subcortical edema. In the chronic stage, there is a marked persistent cortical low intensity on T2-weighted images. This is most prominent in the deeply infolded cortical gyri. The low intensity noted in acute and chronic hemorrhagic cortical infarction with T2 weighting appears to be related to two separate underlying histochemical states. The characteristic cortical low intensity observed on T2-weighted images in acute and chronic hemorrhagic cortical infarction is proportional to the square of the magnetic field strength.